A Review Of The Duluth Gabbro Complex Of Minnesota As A Domestic Source Of Critical And Strategic Metals - Introduction - Stanley N. Watowich (Society for Mining, Metallurgy & Exploration, 1981)
Recently the petroleum market has made us aware that we are indeed global natural resource consumers, and as such, we have become captive to fundamental global resource economics and their attendant vagaries. Global resource supply problems are as old as civilization and mineral exploration one of its important catalysts. On the basis of natural resources empires have been expanded and new frontiers have been developed. Global consumption and production might even be viewed idealistically as a system dedicated to optimizing distribution to the consumer. However, this is not the case. Political instability and increased government polarization make dependency on a global market somewhat insecure. The U.S. must evaluate its domestic mineral re- sources on the basis that all metals are critical and that dependency on even the common and base metals may ultimately weaken our domestic economy and our potential international relationships and could cause critical weaknesses as demonstrated by the petroleum problem. This paper evaluates specifically the Duluth Gabbro Complex, of Northeastern Minnesota, (figure l), as a potential resource of critical and strategic metals. First, a chronology of some of the early exploration, will be followed by more recent intensive company studies and preliminary evaluations of economic feasibility. Lastly, metallurgical data, on some optimum conceptual mining plans will allow metal production data to be compared with an estimate of U.S. domestic needs in 1990. The purpose of this paper is to put into focus the difficulty of converting resources into vitally needed reserves.